"The Legacy Element . . . It Just Felt More Woolly": Exploring the Reasons for the Decline in People With Disabilities' Sport Participation in England 5 Years After the London 2012 Paralympic Games. (October 2018) - Brown, Christopher; Pappous, Athanasios (Sakis)
This article explores why sports participation of people with disabilities in England has declined since the London 2012 Paralympic Games (LPG). Thirty semistructured interviews were conducted with staff employed in a variety of sports and disability-specific organizations. Our preliminary findings suggest that the decline is a result of a complex interplay between multiple factors. A competency gap and a lack of relevance between Paralympians and the rest of the community of people with disabilities might have limited the impact of the legacy. In addition, an absence of coordinated leveraging of the LPG, and a decline in the media coverage of disability sport in the aftermath of the LPG, might also have dulled the legacy. Finally, our data show that austerity and negative media coverage of people with disabilities deterred some people from participating in sport.